On the usefulness of ratios for the identification of some Mediterranean species of the genus Ameles Burmeister, 1838 (Insecta, Mantodea) - Obertegger, Ulrike; Agabiti, Barbara (Zootaxa, 2012)
Identification of Ameles species is a difficult task requiring much experience because of ambiguous descriptions with fewdrawings and great intraspecific morphological variability. Our objective was to find characteristics that could be reliablyused for species identification and would be independent of experience. We identified 12 to 60 specimens of each of 5target species, A. spallanzania (Rossi), A. decolor (Charpentier), A. africana Bolivar, A. picteti (Saussure), A. heldreichiBrunner and 1 to 4 specimens of 7 additional species, A. nana Charpentier, A. kervillei Bolivar, A. modesta Bolivar, A.maroccana Uvarov, A. dumonti Chopard, A. fasciipennis Kaltenbach and A. poggii Lombardo, from the Mediterraneanarea and based on traditional keys. For our analysis, we focused on ten morphological characteristics (lengths of body,pronotum, supracoxal dilatation, fore coxa, fore femur, fore tibia, tegmina, width of the head, minimum width of thepronotum, and maximum width of the fore femur) and five ratios (length to width of the frontal sclerite, pronotum, femur,subgenital plate, and hypophallus), analysed with non-metric multidimensional scaling and linear discriminant analysis.Fewer mis-assignments of species resulted when ratios were used instead of absolute measurements. Among the targetspecies, A. decolor was seldom mis-assigned as another species; A. spallanzania was often mis-assigned as A. africana,while the opposite occurred less frequently; A. picteti was also frequently mis-assigned as A. heldreichi. For the targetspecies, we devised an identification key based on ratios along with morphometric descriptions that appears to work well,because ratios are easily applicable and independent of specimen size. Furthermore, we confirm the synonymy of A.spallanzania and A. africana, recognize that Ameles nana is not a synonym of A. spallanzania, and find that A. poggii is more similar to A. spallanzania than to similar to A. picteti.